2017
DOI: 10.12707/riv16085
|View full text |Cite
|
Sign up to set email alerts
|

Family presence during emergency situations: the opinion of nurses in the adult emergency department

Abstract: ResumoEnquadramento: A presença de familiares no serviço de urgência é uma realidade. Em algumas situações como as de emergência a presença de familiares é algo controverso para os enfermeiros. Objetivos: Conhecer a opinião dos enfermeiros sobre a presença de familiares em situações de emergência no serviço de urgência de adultos. Metodologia: Estudo exploratório descritivo, recorrendo-se à aplicação de um questionário numa amostragem por conveniência. A amostra foi constituída por 233 enfermeiros dos 4 serviç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…However, this may not always occur. Batista et al (2) found that the presence of family members in EDs increased family anxiety and health professional stress levels. The average STAI-S score of the participants in this study reflects a medium anxiety level (mean=49.67).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may not always occur. Batista et al (2) found that the presence of family members in EDs increased family anxiety and health professional stress levels. The average STAI-S score of the participants in this study reflects a medium anxiety level (mean=49.67).…”
Section: Discussionmentioning
confidence: 99%
“…Emergency departments (ED) are the environments that require skilled professionals to take care of critical patients (1,2). Patients and their family members face various problems in the EDs, both in Turkey and over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are frequent in motorcycle accidents, there is a gap in measures or resources capable of preventing or reducing this type of injury. 23 Regarding the characteristics of the participating professionals in the research, those with many years of experience in urgency and emergency stood out; these findings are also revealed in a study developed in Portugal, 24 which can produce a feeling of more security in the care provided in the victims of accidents and in their relatives.…”
Section: Discussionmentioning
confidence: 78%
“…12 This is particularly because many physicians and nurses argue that the practice is controversial, requiring greater depth of knowledge before its implementation. [18][19][20] In Latin America, the scenario is not different. Studies conducted in Chile, 21 Experiences of Family Presence During Emergency Care E3 Colombia, 22 Mexico, 23 Argentina, 24 and Brazil 7,25 point out that the family inclusion in emergency care continues to occur in a variable, inconsistent, and nonsystematized way.…”
mentioning
confidence: 99%
“…However, many health units in these countries still do not follow these recommendations 12. This is particularly because many physicians and nurses argue that the practice is controversial, requiring greater depth of knowledge before its implementation 18–20…”
mentioning
confidence: 99%